Investments - Zvi Bodie (McGraw-Hill Education, 2024)
Investments, Tenth Edition, is intended primarily as a textbook for courses in investment analysis. Our guiding principle has been to present the material in a framework that is organized by a central core of consistent fundamen-tal principles. We attempt to strip away unnecessary math- ematical and technical detail, and we have concentrated on providing the intuition that may guide students and practitioners as they confront new ideas and challenges in their professional lives.